2004
DOI: 10.1111/j.1479-828x.2004.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after a cytological prediction of glandular abnormality

Abstract: These results can be used to inform an evidence-based approach to the investigation and management of abnormal glandular cytology reports. The results can also be used to better inform women about the significance of their abnormal cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This result is similar to the findings in our patients with 13 pathological results: nine cases had premalignant lesions (77%) and four cases had malignant cervical, endometrial or extra‐uterine lesions (23%). In a study by Mitchell, less than 1% of women with minor non‐specific change had cancer 14 . In our study, the incidence of cancer was higher than that reported in their.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to the findings in our patients with 13 pathological results: nine cases had premalignant lesions (77%) and four cases had malignant cervical, endometrial or extra‐uterine lesions (23%). In a study by Mitchell, less than 1% of women with minor non‐specific change had cancer 14 . In our study, the incidence of cancer was higher than that reported in their.…”
Section: Discussionmentioning
confidence: 99%
“…For women with possible high-grade glandular or minor nonspecific changes on Pap smear they found these rates to be 5% and < 1%, respectively. 13 In our study 42 women were referred with AIS on Pap smear and 4 (10%) were diagnosed with an adenocarcinoma in addition to AIS on histology. Thirty-three women had a possible high-grade glandular lesion on their referral Pap smear, 12 with a coexisting high-grade squamous lesion.…”
Section: Correlation Cytology and Histologymentioning
confidence: 72%
“…In a study conducted in Victoria (Australia) 16% of women with AIS on cytology were diagnosed with cancer on histology. 13 This is a high rate in comparison with women with squamous carcinoma in situ on cytology, among whom cancer is diagnosed in about 3-4%. For women with possible high-grade glandular or minor nonspecific changes on Pap smear they found these rates to be 5% and < 1%, respectively.…”
Section: Correlation Cytology and Histologymentioning
confidence: 99%
“…For older women (aged >45 years), a more extensive excision is recommended (at least 25–35 mm) . In this subgroup, 47% (9/19) had an excision of ≤15 mm.…”
Section: Resultsmentioning
confidence: 99%
“…This study confirms the relatively high risk of invasive cancer in women with AIS predicted by cervical cytology, 19.3% in this study. This figure is consistent with national data . Given the high risk of invasive disease associated with index cytology predicting AIS, at a population level, this degree of noncompliance is concerning.…”
Section: Discussionmentioning
confidence: 99%